The Island of Happiness : Tales of Madame d'Aulnoy - Aulnoy, Madame d' (Marie-Catherine), 1650 or 1651-1705 (Book collections on Project MUSE., 2021)
"In this book the visual artist Natalie Frank interprets eight tales by Madame d'Aulnoy, a seventeenth-century French pioneer of the fairy-tale genre. D'Aulnoy is thought to have influenced the development of the literary fairy tale in France and beyond. The tales were written as entertainment for the salons of the time: many contain subtle criticisms of French royalty and aristocrats as well as of enforced social and sexual roles. Her work has been translated into English in the past, but rarely outside of anthologies that include other authors. Frank chose to make d'Aulnoy's tales the subject of this book because "many of her heroines' journeys and conflicts have not changed," she writes. "A suitor's arrogance can destroy happiness; the power of kindness and wiliness, combined with perseverance, triumphs; jealousy poisons families and separates lovers." Frank is deeply interested in the role of women in fairy tales. D'Aulnoy, she says, used her talent to both imagine and inhabit worlds in which women could exercise agency. Aiming to "bridge the gap between fine art and illustration," Frank brings a striking, distinctive style to d'Aulnoy's tales through an integration of art and text. Allegorical, energetic, sometimes grotesque, Frank's art is the focus of this book, accompanied by contemporary English translations of the tales by Jack Zipes, a renowned expert on fairy tales. The book also includes a short essay by the artist on her approach to illustrating the tales, and a general introduction to d'Aulnoy and her work by Zipes"--